Mobile Optical Sensor for Photosynthetic Microbes Quantification - Wong, Ling Shing*; Anthanyomthu, Neesha Sabrina; Lau, Simon Buong Yew; Voon, Betty Wan Niu; Chai, Mee Kin (American Scientific Publishers, 2018)
The quantification of photosynthetic microbes is an important process due to the application of these microbes in various industries. The direct quantification by cell count and indirect quantification through spectrophotometry analysis have been used for decades. The incorporation of ambient light sensor to smart phone enabled the development of a new low cost, portable, and easy to use device for the quantification of photosynthetic microbes. The device is integrated with a special casing with the smart device, which allows the ambient light sensor to be positioned in a straight line with light source and the sample of microbes. The light passes through the sample with the intensity determines by ambient light sensor and displays the value in Lux. The results showed that this tool could determine the quantity of 4 different photosynthetic microbes with good correlation to the number of cells within the range of 7.5 × 105 cells/mL–1.5 × 107 cells/mL. Thus the possibility of using the smart device in the quantification of photosynthetic microbes was confirmed. The new developed device had the advantage of being highly portable, low cost, fast response, and easy to operate. Due to the flexibility in casing design and mobile application programming, more advanced functions and designs could be incorporated into the device in future.